2016
DOI: 10.1177/1524838015585318
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Help Seeking for Lesbian, Gay, Bisexual, Transgender, and Queer Survivors of Intimate Partner Violence

Abstract: Intimate partner violence (IPV) is a pervasive and devastating social problem that is estimated to occur in one of every four opposite-sex relationships and at least one of every five same-sex romantic relationships. These estimates may not represent violence against those who identify as transgender or genderqueer, and very little comprehensive research has been conducted on IPV within these populations. One statewide study on IPV found rates of IPV were as high as one of every two transgender individuals. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
236
1
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(289 citation statements)
references
References 77 publications
(110 reference statements)
6
236
1
16
Order By: Relevance
“…IPV victims can be reluctant in seeking assistance, fearing discrimination (Giorgio, 2002; Helfrich and Simpson, 2006; Carvalho et al, 2011). Rarely a solution was offered to help LGB people in accessing treatment for IPV, and authors recommended modifications to standard treatments or programs (Calton et al, 2015; O’Neal and Parry, 2015). Studies showed that services and shelters were often unprepared to support IPV homosexual and bisexual victims (Buford et al, 2007; Cannon et al, 2016; Barata et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IPV victims can be reluctant in seeking assistance, fearing discrimination (Giorgio, 2002; Helfrich and Simpson, 2006; Carvalho et al, 2011). Rarely a solution was offered to help LGB people in accessing treatment for IPV, and authors recommended modifications to standard treatments or programs (Calton et al, 2015; O’Neal and Parry, 2015). Studies showed that services and shelters were often unprepared to support IPV homosexual and bisexual victims (Buford et al, 2007; Cannon et al, 2016; Barata et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The reviewed literature suggested the need of a psychological treatment designed on specific LGB necessities and finalized to guarantee new useful resources and develop self-determination (Merrill and Wolfe, 2000; Calton et al, 2015; O’Neal and Parry, 2015). Intervention for LGB IPV victims and perpetrators should be part of an integrate and complete treatment plan that can involve couples or individual treatment but, in any case, that should be adapted to each specific situation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal networks are very important for survivors: survivors turn first and most often to friends and family for support for IPV (Sylaska and Edwards 2014;Trotter and Allen 2009). This is especially true for survivors of marginalized backgrounds because of the disparate treatment they can receive from formal sources of support, such as the court systems (Calton et al 2016;Deutsch et al 2017), social service agencies (Kanuha 2005), and law enforcement (Richie 2012;Hirschel et al 2007).…”
Section: Mandatory Reportingmentioning
confidence: 99%
“…Lesbian, gay, bisexual, transgender, and genderqueer (LGBTQ) individuals experience IPV at similar or higher rates than do cisgendered, straight individuals (McKenry, Serovich, Mason, & Mosack. 2006), even with suspected underreporting of IPV among LGBTQ individuals (Calton, Cattaneo, & Gebhard, 2016). Taken together, this suggests that a binary, gender-stereotyped approach to understanding IPV is insufficient to capture the nuances in relationships and patterns of violence.…”
Section: Discussionmentioning
confidence: 99%